Retention of alluvial sediment in the tidal delta of a river draining a small, mountainous coastal watershed. (1st July 2019) - Watson, Elizabeth Burke; Gray, Andrew B.; Pasternack, Gregory B.; Woolfolk, Andrea M.
Abstract: Small mountainous coastal watersheds are thought to be responsible for transporting disproportionately large volumes of sediment to the global ocean. In comparison with low-relief passive margin rivers, their geologic setting is associated with high rates of sediment production, high peak flows due to uniformity in runoff lag-times, and limited floodplain development. However, mountainous watersheds are often associated with estuarine deltas, and because the stream gauges used to calculate water and sediment fluxes tend to be located above the head of tides, the relative magnitude of sediment discharged to the ocean vs. retained in deltas is uncertain. The aim of this study was to determine the estuarine trap efficiency for the Salinas River in central California (USA), a watershed known both for its extremely high rate of sediment production and its extensive lowland delta, thereby helping to resolve the role of estuarine deltas in ocean sediment discharge. Sediment retention rates were calculated for the Late Holocene, using soil maps to estimate the areal extent of the delta prior to land reclamation, and radionuclide, pollen, pollution, and flood chronologies in concert with sediment bulk density measurements to constrain deposition rates. Results suggest that less than 1% of the sediment delivered to the coastal zone by the river was retained in the estuarine delta. Deposition rates distant from distributary channels matched long-term rates of sea level rise, suggesting that the formation of accommodation space acted as a primary control on sediment accretion. However, along tidal-fluvial distributary channels, accretion rates were much greater, and discrete flood layers were present, suggesting that accretion along distributaries was driven by flood events. In addition, long-term variability in sediment accretion rates broadly matched other records of alluvial flooding in central and southern California, suggesting that high precipitation intervals leave an imprint – although subtle – in the sedimentary record of estuaries. By documenting high sediment discharge to the ocean (99% of fluvial load), this study highlights the importance of small mountainous watersheds in global oceanic sediment transport, and further emphasizes the joint roles of accommodation space formation and sediment supply in controlling rates of estuarine sediment accretion. Highlights: <1% of Salinas River sediments were trapped by its delta over the Late Holocene. Away from distributary channels, sediment accumulation rates matched sea level rise. Along tidal-fluvial distributaries, sediment deposition was driven by floods. This high-relief coastal watershed delivers a large volume of sediment to the ocean.